The EU(7)-PIM list: a list of potentially inappropriate medications for older people consented by experts from seven European countries - Renom-Guiteras, Anna; Meyer, Gabriele; Thürmann, Petra A. (European journal of clinical pharmacology, 2015)
Purpose The aim of the study was to develop a European list of potentially inappropriate medications (PIM) for older people, which can be used for the analysis and comparison of prescribing patterns across European countries and for clinical practice. Methods A preliminary PIM list was developed, based on the German PRISCUS list of potentially inappropriate medications and other PIM lists from the USA, Canada and France. Thirty experts on geriatric prescribing from Estonia, Finland, France, the Netherlands, Spain and Sweden participated; eight experts performed a structured expansion of the list, suggesting further medications; twenty-seven experts participated in a two-round Delphi survey assessing the appropriateness of drugs and suggesting dose adjustments and therapeutic alternatives. Finally, twelve experts completed a brief final survey to decide upon issues requiring further consensus. Results Experts reached a consensus that 282 chemical substances or drug classes from 34 therapeutic groups are PIM for older people; some PIM are restricted to a certain dose or duration of use. The PIM list contains suggestions for dose adjustments and therapeutic alternatives. Conclusions The European Union (EU)(7)-PIM list is a screening tool, developed with participation of experts from seven European countries, that allows identification and comparison of PIM prescribing patterns for older people across European countries. It can also be used as a guide in clinical practice, although it does not substitute the decision-making process of individualised prescribing for older people. Further research is needed to investigate the feasibility and applicability and, finally, the clinical benefits of the newly developed list.